Antitumor Effect of KML-B-Treated Dendritic Cells via Induction of Lymphocyte Activation - Jong-Jin Kim; Yun-Ho Hwang; Kyung-Yun Kang; Sung-Ju Lee; Jong-Bae Kim; Jina Choi; Sung-Tae Yee (Journal of Immunology Research)
Lectins are carbohydrate-binding proteins with various biological activities, such as antitumor and immunomodulatory effects. Although lectins have various biological activities, they are still limited by cytotoxicity in normal cells. To overcome this problem, we used the noncytotoxic part of Korean mistletoe lectin B-chain (KML-B) to induce maturation of dendritic cells (DCs). A previous study reported that KML-B induces DC maturation by triggering TLR-4, including expression of costimulatory molecules (CD40, CD80, and CD86), MHC II, and secretion of cytokines in DCs. Additionally, matured DCs by KML-B induced T helper (Th) cell activation and differentiation toward Th1 cells. However, the interaction of KML-B-treated DCs with CD8+ T cells is still poorly understood. In this study, we confirmed the ability of matured DCs by KML-B to stimulate cytotoxic T cells using OT-1 mouse-derived CD8+ T cells. KML-B induced MHC I expression in DCs, stimulation of CD8+ T cell activation and proliferation, and IFN-γ secretion. Moreover, tumor sizes were reduced by KML-B treatment during vaccination of OVA257−264-pulsed DCs. Here, we confirmed induction of CD8+ T cell activation and the antitumor effect of KML-B treatment in DCs.